Selective and Superselective Angiography of Pediatric Moyamoya Disease Angioarchitecture in the Posterior Circulation. Issue 4 (July 2014) - Baltsavias, Gerasimos; Khan, Nadia; Filipce, Venko; Valavanis, Anton
The anastomotic network of the posterior circulation in children with moyamoya disease has not been analyzed. We aimed to investigate the angiographic anatomy of this unique vascular network in patients with childhood moyamoya disease. Selective and superselective injections of the posterior circulation were performed in six children with newly diagnosed moyamoya disease. The arterial branches feeding the moyamoya anastomotic network, their connections and the recipient vessels were demonstrated. Depending on the level of the steno-occlusive lesion, the feeding vessels were the thalamoperforators, the posterior choroidals, the splenic artery, parietoccipital artery, other cortical posterior cerebral artery (PCA) branches, the dural branch of the PCA, the premamillary artery and other posterior communicating artery perforators. Through connections, which are described, the recipient vessels were the striate and medullary arteries, other thalamic arteries with or without medullary extensions, the pericallosal artery, medial parietoccipital cortical branches of the PCA and the anterior choroidal artery. High quality selective and superselective angiography helped in demonstrating the angiographic anatomy of the moyamoya posterior anastomotic network previously either vaguely or incompletely described, as well as connections within the posterior circulation but also its relevance as a collateral to the anterior circulation.